American Commerce, American Empire: Late 19th‐Century Merchant Organizations and Trade Policy. (3rd February 2020) - Davis, Cory
Abstract: The American debate over free trade and protectionism has taken many forms, but it is particularly instructive when it occurs within a single sector of the economy, pitting allied economic interests against each other. That occurred in the shipping industry in the 19 th century when shippers and shipbuilders fought each other over trade‐related questions: subsidies for shipbuilding and reciprocal trade agreements with foreign nations. Shipbuilders wanted protection and subsidies; shippers wanted the freedom to make use of cheaper foreign vessels for trade and to develop trade agreements. We show how these opposing forces stymied each other and prevented the shipping industry from taking an active, unified role in national politics. These particular intra‐industry debates reveal broader divisions within the business community over the relationship between business and government under modern commercial capitalism.